Prensa satírica y poder político - Fausta Gantús (Amnis)
In Mexico, 1876 was characterized by electoral struggle, Tuxtepec revolt and the tense relationships between the government and the press. During this year, the ambitions and interests at the successful military Porfirio Díaz came at odds with those at the audacious politician Sebastián Lerdo de Tejada and their respective partisans. Díaz wanted to concrete his aspirations to become president meanwhile Lerdo pretended to stay in the power. In this context, the press played a fundamental role, especially, the satiric press which functioned as an instrument of political pressure as well as a guide for public opinion. Thus, during 1876 Mexican society was besieged between both factions.